GA2LEN skin test study III: minimum battery of test inhalent allergens needed in epidemiological studies in patients - Bousquet, P. J.; Burbach, G.; Heinzerling, L. M.; Edenharter, G.; Bachert, C.; Bindslev-Jensen, C.; Bonini, S.; Bousquet-Rouanet, L.; Demoly, P.; Bresciani, M.; Bruno, A.; Gjomarkaj, M.; et al. (Allergy, 2009)
The number of allergens to be tested in order to identify sensitized patients is important in order to have the most cost-effective approach in epidemiological studies.|To define the minimal number and the type of skin prick test (SPT) allergens required to identify a patient as sensitized using results of the new Pan-European GA(2)LEN skin prick test study.|In a large Pan-European multicenter (17 centers in 14 countries) patient based study, a standardized panel of 18 allergens has been prick tested using a standardized procedure. Conditional approach allowed to determine the allergens selection.|Among the 3034 patients involved, 1996 (68.2%) were sensitized to at least one allergen. Overall, eight allergens (grass pollen, Dermatophagoides pteronyssinus, birch pollen, cat dander, Artemisia, olive pollen, Blatella and Alternaria) allowed to identified more than 95% of sensitized subjects. However, differences were observed between countries, two allergens being sufficient for Switzerland (grass pollen and cat dander) as opposed to nine for France (grass pollen, Dermatophagoides pteronyssinus, olive pollen, cat dander, Blatella, cypress, dog dander, alder and [Artemisia or Alternaria]). According to country, up to 13 allergens were needed to identify all sensitized subjects.|Eight to ten allergens allowed the identification of the majority of sensitized subjects. For clinical care of individual patients, the whole battery of 18 allergens is needed to appropriately assess sensitization across Europe.
Keywords: Adult Allergens Animals Europe Female Health Surveys Humans Hypersensitivity Male Middle Aged Prevalence Skin Tests Young Adult